Product Modularity, Process Modularity, and New Product Introduction Performance: Does Complexity Matter?. Issue 4 (12th October 2015) - Vickery, Shawnee K.; Koufteros, Xenophon; Dröge, Cornelia; Calantone, Roger
Abstract : Modularity has the potential to impact various facets of new product introduction performance including product development lead time, frequency of new product introduction, on time introduction and product innovation. The impact of modularity on new product introduction performance, however, may vary for different levels of product and process complexity. This study empirically investigates relationships between perceptual measures of product modularity, process modularity, and new product introduction performance and explores whether an objective product/process complexity measure moderates these relationships. Using survey‐based methodology we probe both manufacturers of technically simple products and technically complex products. Hierarchical regression models are used to test hypotheses concerning the main effects of product and process modularity and the effects of their interactions with complexity on new product introduction performance. The results show that the main effect of product modularity was positive and its interaction with complexity was disordinal and negative, suggesting that the positive effect of product modularity on new product introduction performance is dampened when complexity is high. For process modularity, only the interaction effect (positive) was statistically significant and it was also disordinal in nature. Thus, the effect of process modularity on new product introduction performance is heightened when complexity is high. The implications of these findings are discussed and more specific theoretical and managerial implications are delineated by examining the impacts of these main and interaction effects on individual measures of new product introduction performance (frequency of new product introduction, product development lead times, product innovation, and on‐time product launch).